Lesson Plan Design based on the Kurikulum Merdeka by English Teachers at UNP Laboratory Junior High School - Dwi Wahyuni; Sitti Fatimah (Journal of English Language Teaching, 2023)
This research aimed to investigate the suitability of the Lesson plan design based on the Kurikulum Merdeka by English Teachers and also their understanding of the Lesson Plan at UNP Laboratory Junior High School. Two teachers at UNP Laboratory Junior High School were assigned to given their Lesson plan design and were interviewed about their understanding of the Lesson plan. Qualitative analyses were employed in the research which using qualitative descriptive approach to describe the suitability analysis of the Lesson plan design by English Teachers, while data from interview were transcribed, classified and the draw conclusion. The result from the qualitative suitability analysis showed that the Lesson plan design by English Teachers at UNP Laboratory Junior High School quite an accordance, the Lesson plan has the complete components although it has some drawbrack. The interview result showed that teachers understanding of the Lesson plan is good. Even the teachers has good understanding in the Lesson plan but they still need training in designing Lesson plan, so the teacher will be more prepared in designing Lesson plan based on the Kurikulum Merdeka.